Efektivitas Malay Eco Culture Project berbasis Pembelajaran Bermakna terhadap Interaksi Sosial Anak Usia Dini - Siti Fadillah; Heleni Filtri; Suharni Suharni; Sri Purwasih; Debby Muslihatun (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to analyze the effectiveness of the Eco Culture Project based on meaningful learning on the social interactions of early childhood children in Pembina 3 Pekanbaru State Kindergarten. This study uses a quantitative approach with a quasi-experimental method through a pretest-posttest control group design. The research subjects were 60 early childhood children consisting of 30 children in the experimental class and 30 children in the control class. The experimental class received treatment in the form of Eco Culture Project activities based on meaningful learning, while the control class followed regular learning. Data were collected through observation sheets for children's social interactions consisting of 26 indicators, including the ability to cooperate, communicate, share, respect friends, obey rules, and participate in group activities. The results of the study in the experimental class showed an increase in children's social interactions after being given treatment. The total pretest score of the experimental class was 1,498 with a percentage of 48.01%, increasing to 2,436 with a percentage of 78.08% in the posttest. The average increase in scores was 31.27 points with an N-Gain value of 0.58 which is included in the moderate category. The results of the paired sample t-test showed a significant difference between the pretest and posttest scores of the experimental class with a significance value of p < 0.001. Thus, the Eco Culture Project based on meaningful learning is effective in improving social interactions in early childhood. These findings indicate that project activities that integrate environmental exploration, local culture, group work, and reflection on learning experiences can create contextual, collaborative, and meaningful learning for children's social development.